Pregnancy and obstetric outcomes of dichorionic and trichorionic triamniotic triplet pregnancy with multifetal pregnancy reduction: a retrospective analysis study - Shuhua Liu; Guanjian Li; Chao Wang; Ping Zhou; Zhaolian Wei; Bing Song (BMC, 2022)
Abstract Background It is generally beneficial for triplet gestation or high-order multiple pregnancies to operate multifetal pregnancy reduction (MFPR) after assisted reproductive techniques. However, data on pregnancy outcomes is lacking regarding dichorionic triamniotic (DCTA) and trichorionic triplets (TCTA) pregnancy. Method This research analyzes the difference between 128 DCTA and 179 TCTA pregnancies with or without MFPR after in vitro fertilization/intracytoplasmic sperm injection cycles between January 2015 and June 2020. The subdivided subgroups of the two groups are reduction to singleton, reduction to dichorionic twins, and expectant management groups. We also compare the pregnancy and obstetric outcomes between 2104 dichorionic twins and 122 monochorionic twins. Result The research subgroups were DCTA to monochorionic singleton pregnancies (n = 76), DCTA to dichorionic twin pregnancies (n = 18), DCTA-expectant management (n = 34), TCTA to monochorionic singleton pregnancies (n = 31), TCTA to dichorionic twin pregnancies (n = 130), and TCTA-expectant management (n = 18). In DCTA-expectant management group, the complete miscarriage rate is dramatically higher, and the survival rate and the rate of take-home babies are lower. However, there was no difference between the rates of complete miscarriages, survival rates, and take-home babies in TCTA-expectant management group. But the complete miscarriage rate of DCTA-expectant management was obviously higher than that of TCTA-expectant management group (29.41 vs. 5.56%, p = 0.044). For obstetric outcomes, MFPR to singleton group had higher gestational week and average birth weight, but lower premature delivery, gestational hypertension rates and low birth weight in both DCTA and TCTA pregnancy groups (all p < 0.05). DCTA to monochorionic singleton had the lowest incidence of gestational diabetes, whereas The subdivided subgroups of TCTA had no significant difference in the incidence of gestational diabetes. Monochorionic twins have higher rates of complete, early, and late miscarriage, premature delivery, and late premature delivery, and lower survival rate (p < 0.05). Conclusion MFPR could improve gestational week and average birth weight, reducing premature delivery, LBW, and gestational hypertension rates in DCTA and TCTA pregnancies. Monochorionic twins have worse pregnancy and obstetric outcomes. MFPR to singleton is preferable recommended in the pregnancy and obstetric management of complex triplets with monochorionic pair.